Knowledge, Attitude, and Practice (KAP) of Pharmacists about Natural Products Used for Urolithiasis in Shiraz, Iran - Kowsar Danesh; Saeid Daneshamouz; Iman Karimzadeh; Abdolali Mohagheghzadeh* (Research Journal of Pharmacognosy, 2023)
Background and objectives: We wanted to figure out how pharmacists make their judgments about the efficacy of natural products in urolithiasis and how they make suggestions about these products. Methods: A self-made descriptive questionnaire was designed, evaluated, and performed to assess pharmacists’ knowledge, attitude, and practice (KAP) about natural products in urolithiasis in 46 young pharmacists and final year pharmacy students in Shiraz. Results: In all of the KAP sections, Rowatinex®, Cystone®, and Sankol® were the most known, believed to be effective, and preferred pharmacist products. Respondents had received different education hours. About 54% of them believed their education was averagely adequate. Brochures (63.0%), web-search (60.9%), and applications (45.7%) were the primary resources used by pharmacists, mainly to check the instruction of use. About 80% of pharmacists were unaware of the mechanism of action of at least 5 of 14 products. Generally, respondents had a positive view of natural products. In addition, they thought price and advertisements were effective in patients’ and physicians’ choice of products. More than half of pharmacists preferred to use clinical trials (52.2%) rather than systematic reviews (19.6%). Conclusion: Providing a vast amount of information in the education process is not the best solution for preparing pharmacists for their role in community pharmacies. Besides the need for increasing clinical trials about complementary and alternative medicines and developing evidence-based databases, we need to train pharmacy students in professional ways to gain knowledge about complementary and alternative medicines.